Can the neck contribute to persistent symptoms post concussion? Long-term follow up from a prospective descriptive case series. (3rd September 2021) - Kennedy, Ewan; Chapple, Cathy; Quinn, Dusty; Tumilty, Steve
ABSTRACT: Objective: To describe individual long-term outcomes of people with persistent symptoms following a concussion who received neck treatment as part of multidisciplinary concussion care. A secondary objective is to report on how participants describe the outcomes of neck treatmentMethods: Long-term follow-up for a subgroup of participants in a prospective case series (n = 11). Data were collected at initial assessment, completion of neck treatment, 6 and 12 months including standard questionnaires (Rivermead post-concussion symptoms questionnaire, neck disability index, dizziness handicap inventory); patient-reported measures of headache, dizziness and neck pain and participant descriptions of the effects of neck treatmentResults: Grouped measures of post-concussion symptoms were further improved or sustained at 6 and 12 months. Ten of the 11 participants reported neck treatment as a beneficial part of their care and described the effects on the neck, multiple symptoms and their overall recovery. However, seven participants experienced recurrent headache, neck pain or dizziness at 6- or 12-month follow-up.Conclusion: Long-term follow-up of individuals receiving neck treatment shows improvement across a range of patient reported outcomes, yet highlights frequent recurrence of symptoms. Neck treatment can play a valuable role in people's recovery that extends beyond local effects on the neck.